Data Policy: A Conceptual Framework - Renda, Andrea (IE Center for the Governance of Change, 2023)
The first policy paper offers a conceptual framework to address the elusive economics of data and a decalogue for policymakers to optimize the value of data flows, highlighting the need for tailored approaches based on data's utility function.
Keywords: Data policy; policymakers